2008
DOI: 10.1111/j.1469-8137.2008.02571.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet radiation drives methane emissions from terrestrial plant pectins

Abstract: Summary• Recent studies demonstrating an in situ formation of methane (CH 4 ) within foliage and separate observations that soil-derived CH 4 can be released from the stems of trees have continued the debate about the role of vegetation in CH 4 emissions to the atmosphere. Here, a study of the role of ultraviolet (UV) radiation in the formation of CH 4 and other trace gases from plant pectins in vitro and from leaves of tobacco (Nicotiana tabacum) in planta is reported.• Plant pectins were investigated for CH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
208
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(226 citation statements)
references
References 48 publications
14
208
2
2
Order By: Relevance
“…soil or plant water) and whether plants have their own mechanism(s) to produce CH 4 have been debated (Bruhn et al, 2012;Keppler et al, 2009;Nisbet et al, 2009). Evidence is now accumulating to indicate that plants can produce CH 4 even in the presence of oxygen (Bruggemann et al, 2009;Bruhn et al, 2009Bruhn et al, , 2014Cao et al, 2008;Fraser et al, 2015;Keppler et al, 2008;Lenhart et al, 2014;McLeod et al, 2008;Messenger et al, 2009;Mikkelsen et al, 2011;Reid, 2009, 2011;Sanhueza and Donoso, 2006;Sinha et al, 2007;Vigano et al, 2009Vigano et al, , 2008Wang et al, 2009aWang et al, , 2009bWang et al, , 2011aWatanabe et al, 2012;Wishkerman et al, 2011).…”
Section: Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…soil or plant water) and whether plants have their own mechanism(s) to produce CH 4 have been debated (Bruhn et al, 2012;Keppler et al, 2009;Nisbet et al, 2009). Evidence is now accumulating to indicate that plants can produce CH 4 even in the presence of oxygen (Bruggemann et al, 2009;Bruhn et al, 2009Bruhn et al, , 2014Cao et al, 2008;Fraser et al, 2015;Keppler et al, 2008;Lenhart et al, 2014;McLeod et al, 2008;Messenger et al, 2009;Mikkelsen et al, 2011;Reid, 2009, 2011;Sanhueza and Donoso, 2006;Sinha et al, 2007;Vigano et al, 2009Vigano et al, , 2008Wang et al, 2009aWang et al, , 2009bWang et al, , 2011aWatanabe et al, 2012;Wishkerman et al, 2011).…”
Section: Plantsmentioning
confidence: 99%
“…The impacts of UV radiation and heating on CH 4 emissions from detached leaves (Bruhn et al, 2009;Fraser et al, 2015;McLeod et al, 2008;Reid, 2009, 2011;Vigano et al, 2009Vigano et al, , 2008Wang et al, 2011b), intact plants and structural components (e.g. pectin, lignin, cellulose and leaf surface wax) (Bruhn et al, 2014;Keppler et al, 2008;McLeod et al, 2008;Messenger et al, 2009;Vigano et al, 2009Vigano et al, , 2008 have been extensively tested.…”
Section: Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that CH 4 can be produced abiotically from plant material by exposing it to ultraviolet (UV) irradiation [15][16][17][18] . A reaction of reactive oxygen species (ROS) with methoxyl groups of pectic polysaccharides was suggested as a possible route to CH 4 formation under UV radiation 19 .…”
mentioning
confidence: 99%
“…soil moisture and soil temperature) caused by environmental treatments, which may control CH 4 fluxes by regulating methanogenesis and oxidation processes (Pearce & Clymo 2001;Zhuang et al 2007). Therefore, plant-derived CH 4 emission is still questioned because limited evidence of the chemical mechanism has been identified to account for the process McLeod et al 2008;Vigano et al 2008;Messenger et al 2009). Using a closed, opaque chamber technique, we conducted an experiment with four treatments during the growing seasons of 2007 and 2008 to examine the hypothesis that abiotic (i.e.…”
Section: Introductionmentioning
confidence: 99%